Composite material photovoltaic cable bridge and preparation method and application thereof

By using composite materials such as epoxy resin, carbon fiber, modified yttrium oxide hollow microspheres and intercalated nanoplastics, the problems of degradation of water absorption and mechanical properties of existing photovoltaic cable trays are solved, and higher barrier properties, tensile strength and flame retardant grade are achieved.

CN119775710APending Publication Date: 2025-04-08JIANGXI LONGZHENG TECH DEV CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411329307.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing photovoltaic cable tray uses epoxy resin as the matrix, which has problems such as high water absorption and degraded mechanical strength and electrical insulation performance, which affects the service life and safety of the product.

Method used

Using a composite material of 70 parts of epoxy resin, 20 parts of carbon fiber, 3-5 parts of modified yttrium oxide hollow microspheres, 2-4 parts of intercalated nanoplastics, 1-3 parts of plasticizer, 0.2-0.4 parts of defoaming agent, 0.3-0.5 parts of antioxidant and 1-2 parts of flame retardant, the permeability of water molecules is extended through the multi-layer structure of modified yttrium oxide hollow microspheres, the permeability of water molecules is enhanced, and the electrical insulation and compressive strength are improved, and the flame retardant grade and toughness are improved through intercalated nanoplastics.

Benefits of technology

The barrier properties, tensile strength and flame retardant grade of composite photovoltaic cable tray are significantly improved, the water absorption rate is reduced, and the stability and compressive strength in humid environments are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775710A_ABST
    Figure CN119775710A_ABST
Patent Text Reader

Abstract

The invention provides a composite material photovoltaic cable bridge and a preparation method and application of the composite material photovoltaic cable bridge, and belongs to the technical field of composite material products. The material is prepared from the following components in parts by weight: 70 parts of epoxy resin, 20 parts of carbon fibers, 3-5 parts of modified yttrium oxide hollow microspheres, 2-4 parts of intercalated nano plastic, 1-3 parts of a plasticizer, 0.2-0.4 part of a defoaming agent, 0.3-0.5 part of an antioxidant and 1-2 parts of a flame retardant. The multilayer structure formed by the modified yttrium oxide hollow microspheres in the epoxy resin matrix obviously prolongs the permeation path of water molecules and increases the permeation difficulty of the water molecules, so that the barrier property of the composite material photovoltaic cable bridge is improved, the water absorption rate of the composite material photovoltaic cable bridge is reduced, and the service life of the composite material photovoltaic cable bridge is prolonged. The stability of the composite material in a humid environment is improved, namely, the electrical insulating property and the compressive strength of the composite material photovoltaic cable bridge are kept stable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of composite material products, and in particular relates to a composite material photovoltaic cable bridge and a preparation method and application thereof. Background Art

[0002] Photovoltaic cable trays are facilities used to support and protect cables in photovoltaic power generation systems. Their design and installation quality directly affect the safety, stability and convenience of subsequent maintenance of the power station. Photovoltaic cable trays can be divided into trough-type cable trays, tray-type cable trays and ladder-type cable trays according to their structural form.

[0003] Among the composite materials used in existing photovoltaic cable bridges, epoxy resin is used as the matrix. Epoxy resin has excellent adhesion, mechanical strength, electrical insulation and chemical stability. However, epoxy resin has high water absorption. After absorbing water, the mechanical strength and electrical insulation properties of epoxy resin will be significantly reduced, affecting the service life and safety of the product. At the same time, the epoxy resin cured product is usually brittle and easy to break. That is, the composite material with epoxy resin as the matrix is ​​relatively brittle and easy to break. Summary of the invention

[0004] In order to solve the problems existing in the background technology, the present invention provides a composite material photovoltaic cable bridge and a preparation method and application thereof.

[0005] In order to achieve the above-mentioned purpose, in a first aspect, the present invention provides a composite material photovoltaic cable bridge, comprising the following components, calculated by weight: 70 parts of epoxy resin, 20 parts of carbon fiber, 3-5 parts of modified yttrium oxide hollow microspheres, 2-4 parts of intercalated nanoplastics, 1-3 parts of plasticizer, 0.2-0.4 parts of defoaming agent, 0.3-0.5 parts of antioxidant and 1-2 parts of flame retardant.

[0006] Furthermore, the preparation method of the modified yttrium oxide hollow microspheres is as follows:

[0007] A1. Preparation of monodisperse melamine-formaldehyde microspheres: 9.8 g of formaldehyde solution and 200 mL of water were added to a flask, stirred magnetically, and heated in a water bath to 80°C; then, 2.5 g of melamine was added to the flask, and after the melamine was completely dissolved, formic acid was added to adjust the pH value of the system in the flask to 6; after one minute, the transparent solution became turbid, and stirring was continued for 15 minutes to obtain a milky white solution; the obtained solution was washed three times by centrifugation with water and ethanol respectively, and dried at 60°C to obtain melamine-formaldehyde template microspheres for use;

[0008] A2, add 0.8mmol of yttrium nitrate hexahydrate into a small beaker containing 30mL of deionized water, and stir magnetically to dissolve the yttrium nitrate hexahydrate; then add 3g of urea into the small beaker, and after a clear solution is formed, add 0.2g of the melamine-formaldehyde template microspheres in step A1, and ultrasonically treat for 25 minutes to obtain a mixed solution; transfer the mixed solution to a flask, heat it to 85°C in a water bath, and stir to react for 2.8 hours; wash the obtained sample with water and ethanol by centrifugation for several times, and dry it at 60°C to obtain composite microspheres; calcine the composite microspheres for a period of time to obtain white powder;

[0009] A3, acid etching treatment: the white powder obtained in step A2 is placed in 0.1 mol / L hydrochloric acid at a temperature of 43°C for 25 minutes, then washed twice with deionized water and dried at 60°C to obtain modified yttrium oxide hollow microspheres.

[0010] Furthermore, in A1, the speed of magnetic stirring is 62-75 r / min; in A2, the speed of magnetic stirring is 45-55 r / min, and the composite microspheres are calcined at 800° C. for 2 hours to obtain white powder, and the heating rate is 2° C. / min.

[0011] Furthermore, the preparation method of the intercalated nanoplastic is as follows:

[0012] B1. In a 1000mL flask, add 600mL of distilled water, weigh 30g of sodium montmorillonite, add it to the flask, and heat it; weigh 10g of 1831 intercalation agent, add it when the montmorillonite suspension is heated to 80°C, react at constant temperature for 2h, pour it out, wash it with distilled water until it is neutral, filter it, dry it at 80°C, crush it with a universal grinder to obtain powder d, sieve it, and set it aside;

[0013] B2, under nitrogen protection, add 100mL of heptane into the flask, add 20g of d powder under magnetic stirring at a speed of 70r / min, and slowly add 30mL of heptane solution containing 0.5g of 2,6-diacetylpyridine-bis-2,4,6-trimethylanilino ferric chloride catalyst dropwise to the montmorillonite heptane suspension at room temperature, and react for 6h to obtain a slurry;

[0014] B3. Empty the 2L polymerization reactor with nitrogen, add 0.5L hexane into the polymerization reactor, and add the slurry obtained in B2 and 0.6g of co-catalyst AlEt3 in sequence under the flow of hexane under magnetic stirring at 300r / min. Stop adding when 1L of hexane is added; close the vent valve, introduce ethylene gas at a predetermined polymerization temperature, the polymerization temperature is 75°C, the polymerization pressure is 1.0MPa, the polymerization time is 2 hours, open the vent valve, cool down, and discharge the material; filter the polymer, wash it with 95% ethanol, and then vacuum dry it at 60°C to obtain intercalated nanoplastics.

[0015] Furthermore, the plasticizer includes a stearate plasticizer or a phthalate plasticizer.

[0016] Furthermore, the antioxidant includes a phenolic antioxidant or an amine antioxidant.

[0017] Furthermore, the defoaming agent is polydimethylsiloxane.

[0018] Furthermore, the flame retardant is a mixture of hexabromocyclododecane, aluminum oxide and ammonium polyphosphate in a mass ratio of 1:1:2.

[0019] In a second aspect, the present invention provides a method for preparing the composite photovoltaic cable bridge, comprising the following steps:

[0020] S1. Evenly mix 70 parts of epoxy resin, 20 parts of carbon fiber, 3-5 parts of modified yttrium oxide hollow microspheres, 2-4 parts of intercalated nanoplastics, 1-3 parts of plasticizer, 0.2-0.4 parts of defoamer, 0.3-0.5 parts of antioxidant, and 1-2 parts of flame retardant, and mix at a mixing temperature of 160-171° C. to obtain a blend;

[0021] S2, conveying the blend of step S1 to a twin-screw extruder, and granulating at a working temperature of 160-180° C. to obtain a composite material;

[0022] S3, sending the composite material obtained in step S2 into an injection molding machine, melting it at 170-180° C., injecting it into a mold, and cooling it to obtain a composite material photovoltaic cable bridge.

[0023] In a third aspect, the present invention provides an application of the above-mentioned composite material photovoltaic cable bridge, wherein the composite material photovoltaic cable bridge is used as a supporting structure of a photovoltaic cable.

[0024] This application has the following beneficial effects:

[0025] 1. The multilayer structure formed by the modified yttrium oxide hollow microspheres in the epoxy resin matrix significantly prolongs the penetration path of water molecules and increases the difficulty of water molecules to penetrate, thereby improving the barrier properties of the product, reducing the water absorption rate, and improving the stability in a humid environment, that is, the electrical insulation and compressive strength of the product remain stable; when the crack encounters the modified yttrium oxide hollow microspheres, the direction of the crack will be deflected, extending the crack path, and increasing the ability of the product to resist fracture, that is, improving the tensile strength of the composite photovoltaic cable bridge; the modified yttrium oxide hollow microspheres improve the overall tensile strength of the product by strengthening the connection inside the epoxy resin matrix, making it more difficult to be broken.

[0026] 3. Modified yttrium oxide hollow microspheres provide physical insulation, epoxy resin forms a chemical carbon layer, and intercalated nanoplastics enhance the barrier properties of the carbon layer. Epoxy resin, modified yttrium oxide hollow microspheres and intercalated nanoplastics complement each other in structure and jointly build a powerful flame retardant system to improve the flame retardant grade.

[0027] 4. The nanoplastic layer can provide additional strength, and when these plastic layers exist in the form of intercalation, they can disperse stress more effectively. At the same time, epoxy resin, modified yttrium oxide hollow microspheres and intercalated nanoplastics work together to improve toughness. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 , a comparative trend diagram of the insulation properties (dielectric constants) of the products obtained in Examples 1-4 of the present invention and Comparative Examples 1-5;

[0029] Figure 2 , a comparative trend chart of the mechanical properties (compressive strength) of the products obtained in Examples 1-4 of the present invention and Comparative Examples 1-5;

[0030] Figure 3 The figure is a comparison trend chart of the mechanical properties (tensile strength) of the products obtained in Examples 1-4 of the present invention and Comparative Examples 1-5;

[0031] Figure 4 This is a comparative trend chart of the toughness (impact strength) of the products obtained in Examples 1-4 of the present invention and Comparative Examples 1-5. DETAILED DESCRIPTION

[0032] The present application is further described in detail below with reference to the embodiments.

[0033] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present application are all commercially available.

[0034] Example 1: A composite photovoltaic cable bridge comprises the following components, calculated by weight: 70 parts of epoxy resin, 20 parts of carbon fiber, 4 parts of modified yttrium oxide hollow microspheres, 3 parts of intercalated nanoplastics, 2 parts of plasticizer, 0.3 parts of defoaming agent, 0.4 parts of antioxidant and 1.5 parts of flame retardant.

[0035] The epoxy resin is Japanese Mitsubishi JER epoxy resin 1256, and the plasticizer is a stearate plasticizer, specifically zinc stearate, which can also act as a heat stabilizer. The carbon fiber is chopped carbon fiber (model 12358), purchased from Dongyi Yang (Jinan) New Materials Co., Ltd. The antioxidant is a phenolic antioxidant, specifically antioxidant 2246, which is a bisphenol structure antioxidant with the advantages of reduced volatility and better effect. The defoamer is polydimethylsiloxane. The flame retardant is a mixture of hexabromocyclododecane, aluminum oxide, and ammonium polyphosphate in a mass ratio of 1:1:2.

[0036] A method for preparing a composite photovoltaic cable bridge comprises the following steps:

[0037] S1, 70 parts of epoxy resin, 20 parts of carbon fiber, 4 parts of modified yttrium oxide hollow microspheres, 3 parts of intercalated nanoplastics, 2 parts of plasticizer, 0.3 parts of defoamer, 0.4 parts of antioxidant and 1.5 parts of flame retardant are mixed uniformly, and the mixing temperature reaches 160-171° C. to obtain a blend;

[0038] S2, conveying the blend of step S1 to a twin-screw extruder, and granulating at a working temperature of 160-180° C. to obtain a composite material;

[0039] S3, sending the composite material obtained in step S2 into an injection molding machine, melting it at 170-180° C., injecting it into a mold, and cooling it to obtain a composite material photovoltaic cable bridge.

[0040] The preparation method of the modified yttrium oxide hollow microspheres is as follows:

[0041] A1. Preparation of monodisperse melamine-formaldehyde microspheres: 9.8 g of formaldehyde solution and 200 mL of water were added to a flask, and magnetic stirring was performed at a speed of 62 r / min for 25 minutes; the mixture was heated in a water bath to 80°C; then, 2.5 g of melamine was added to the flask, and after the melamine was completely dissolved, formic acid was added to adjust the pH value of the system in the flask to 6; after one minute, the transparent solution became turbid, and stirring was continued for 15 minutes to obtain a milky white solution; the obtained solution was washed by centrifugation with water and ethanol for 3 times, respectively, and dried at 60°C to obtain melamine-formaldehyde template microspheres for use;

[0042] A2, add 0.8mmol of yttrium nitrate hexahydrate into a small beaker containing 30mL of deionized water, and stir magnetically to dissolve the yttrium nitrate hexahydrate; the speed of magnetic stirring is 45r / min, and the stirring time is 20 minutes; then add 3g of urea into the small beaker, and after a clear solution is formed, add 0.2g of melamine-formaldehyde template microspheres in step A1, and ultrasonically treat for 25 minutes to obtain a mixed solution; transfer the mixed solution to a flask, heat it to 85°C in a water bath, and stir to react for 2.8 hours; wash the obtained sample with water and ethanol by centrifugation for several times, and dry it at 60°C to obtain composite microspheres; the composite microspheres are calcined at 800°C for 2 hours to obtain a white powder, and the heating rate is 2°C / min to obtain a white powder;

[0043] A3, acid etching treatment: the white powder obtained in step A2 is placed in 0.1 mol / L hydrochloric acid at a temperature of 43°C for 25 minutes, then washed twice with deionized water and dried at 60°C to obtain modified yttrium oxide hollow microspheres.

[0044] Among them, melamine, analytical grade, was purchased from Sinopharm Chemical Reagent Co., Ltd.; formaldehyde, analytical grade, was purchased from Xilong Chemical Co., Ltd.; formic acid, analytical grade, was purchased from Nanjing Chemical Reagent Co., Ltd.; urea, analytical grade, was purchased from Sinopharm Chemical Reagent Co., Ltd.; yttrium nitrate hexahydrate, analytical grade, was purchased from Sinopharm Chemical Reagent Co., Ltd.

[0045] The preparation method of the intercalated nano plastic is as follows:

[0046] B1. In a 1000mL flask, add 600mL of distilled water, weigh 30g of sodium montmorillonite, add it to the flask, and heat it; weigh 10g of 1831 intercalation agent, add it when the montmorillonite suspension is heated to 80°C, react at constant temperature for 2h, pour it out, wash it with distilled water until it is neutral, filter it, dry it at 80°C, crush it with a universal grinder to obtain powder d, sieve it, and set it aside;

[0047] B2. Under nitrogen protection, 100 mL of heptane was added to the flask, and 20 g of d powder was added under magnetic stirring at a speed of 70 r / min. At room temperature, 30 mL of a heptane solution containing 0.5 g of 2,6-diacetylpyridine-bis-2,4,6-trimethylanilino ferric chloride catalyst was slowly added dropwise to the montmorillonite heptane suspension, and the mixture was reacted for 6 h to obtain a slurry.

[0048] B3, evacuate the 2L polymerization reactor with nitrogen, add 0.5L hexane into the polymerization reactor, add the slurry obtained in B2 and 0.6g of co-catalyst AlEt3 under the flow of hexane under magnetic stirring at 300r / min, stop adding when 1L of hexane is added; close the vent valve, pass ethylene gas at the predetermined polymerization temperature, the polymerization temperature is 75°C, the polymerization pressure is 1.0MPa, the polymerization time is 2h, open the vent valve, cool down, and discharge. Filter the polymer, wash with 95% ethanol, and vacuum dry at 60°C to obtain MMT / polyethylene nanoplastics, i.e., intercalated nanoplastics.

[0049] Among them, montmorillonite is made from Ye Baishou Hongshan bentonite mine; octadecyltrimethylammonium chloride, referred to as 1831 intercalation agent, industrial grade, purchased from Shanghai Jingwei Chemical Company; ethylene, polymerization grade, purchased from PetroChina Liaoyang Petrochemical Branch; hexane, industrial grade, purchased from PetroChina Liaoyang Petrochemical Branch; industrial grade nitrogen, purchased from PetroChina Liaoyang Petrochemical Branch.

[0050] Example 2: The difference between this example and Example 1 is that the proportions of the raw material components used to prepare the composite material photovoltaic cable bridge are different.

[0051] The details are as follows: A composite material photovoltaic cable bridge, including the following components, calculated by weight: 70 parts of epoxy resin, 20 parts of carbon fiber, 3 parts of modified yttrium oxide hollow microspheres, 2 parts of intercalated nanoplastics, 1 part of plasticizer, 0.2 parts of defoaming agent, 0.3 parts of antioxidant, and 1 part of flame retardant.

[0052] A method for preparing a composite photovoltaic cable bridge comprises the following steps:

[0053] S1, 70 parts of epoxy resin, 20 parts of carbon fiber, 3 parts of modified yttrium oxide hollow microspheres, 2 parts of intercalated nanoplastics, 1 part of plasticizer, 0.2 parts of defoamer, 0.3 parts of antioxidant and 1 part of flame retardant are mixed evenly, and the mixing temperature reaches 160-171° C. to obtain a blend;

[0054] S2, conveying the blend of step S1 to a twin-screw extruder, and granulating at a working temperature of 160-180° C. to obtain a composite material;

[0055] S3, sending the composite material obtained in step S2 into an injection molding machine, melting it at 170-180° C., injecting it into a mold, and cooling it to obtain a composite material photovoltaic cable bridge.

[0056] Example 3: The difference between this example and Example 1 is that the proportions of the raw material components used to prepare the composite material photovoltaic cable bridge are different.

[0057] The details are as follows: A composite material photovoltaic cable bridge, including the following components, calculated by weight: 70 parts of epoxy resin, 20 parts of carbon fiber, 5 parts of modified yttrium oxide hollow microspheres, 4 parts of intercalated nanoplastics, 3 parts of plasticizer, 0.4 parts of defoaming agent, 0.5 parts of antioxidant, and 2 parts of flame retardant.

[0058] A method for preparing a composite photovoltaic cable bridge comprises the following steps:

[0059] S1, 70 parts of epoxy resin, 20 parts of carbon fiber, 5 parts of modified yttrium oxide hollow microspheres, 4 parts of intercalated nanoplastics, 3 parts of plasticizer, 0.4 parts of defoamer, 0.5 parts of antioxidant and 2 parts of flame retardant are mixed uniformly, and the mixing temperature reaches 160-171°C to obtain a blend;

[0060] S2, conveying the blend of step S1 to a twin-screw extruder, and granulating at a working temperature of 160-180° C. to obtain a composite material;

[0061] S3, sending the composite material obtained in step S2 into an injection molding machine, melting it at 170-180° C., injecting it into a mold, and cooling it to obtain a composite material photovoltaic cable bridge.

[0062] Example 4: The difference between this example and Example 1 is that the speed of magnetic stirring in the preparation method of modified yttrium oxide hollow microspheres is different, as follows:

[0063] The preparation method of the modified yttrium oxide hollow microspheres is as follows:

[0064] A1. Preparation of monodisperse melamine-formaldehyde microspheres: 9.8 g of formaldehyde solution and 200 mL of water were added to a flask, and magnetic stirring was performed at a speed of 75 r / min for 25 minutes; the mixture was heated in a water bath to 80°C; then, 2.5 g of melamine was added to the flask, and after the melamine was completely dissolved, formic acid was added to adjust the pH value of the system in the flask to 6; after one minute, the transparent solution became turbid, and stirring was continued for 15 minutes to obtain a milky white solution; the obtained solution was washed three times by centrifugation with water and ethanol respectively, and dried at 60°C to obtain melamine-formaldehyde template microspheres for use;

[0065] A2, add 0.8mmol of yttrium nitrate hexahydrate into a small beaker containing 30mL of deionized water, and stir magnetically to dissolve the yttrium nitrate hexahydrate; the speed of magnetic stirring is 55r / min, and the stirring time is 20 minutes; then add 3g of urea into the small beaker, and after a clear solution is formed, add 0.2g of melamine-formaldehyde template microspheres in step A1, and ultrasonically treat for 25 minutes to obtain a mixed solution; transfer the mixed solution to a three-necked flask, heat it to 85°C in a water bath, and stir to react for 2.8 hours; wash the obtained sample with water and ethanol by centrifugation for several times, and dry it at 60°C to obtain composite microspheres; the composite microspheres are calcined at 800°C for 2 hours to obtain white powder, and the heating rate is 2°C / min to obtain white powder;

[0066] A3, acid etching treatment: the white powder obtained in step A2 was placed in 0.1 mol / L hydrochloric acid, treated at 43°C for 25 minutes, then washed twice with deionized water, and dried at 60°C to obtain modified yttrium oxide hollow microspheres.

[0067] Comparative Example 1: The only difference between this comparative example and Example 1 is that the modified yttrium oxide hollow microspheres are replaced by yttrium oxide, specifically as follows: A composite material photovoltaic cable tray, comprising the following components, calculated in parts by weight: 70 parts of epoxy resin, 20 parts of carbon fiber, 4 parts of yttrium oxide, 2 parts of plasticizer, 0.3 parts of defoaming agent, 0.4 parts of antioxidant and 1.5 parts of flame retardant.

[0068] Comparative Example 2: The only difference between this comparative example and Example 1 is that the modified yttrium oxide hollow microspheres are deleted. Specifically, a composite photovoltaic cable bridge comprises the following components, calculated by weight: 70 parts of epoxy resin, 20 parts of carbon fiber, 3 parts of intercalated nanoplastic, 2 parts of plasticizer, 0.3 parts of defoaming agent, 0.4 parts of antioxidant and 1.5 parts of flame retardant.

[0069] Comparative Example 3: The difference between this comparative example and Example 1 is that the intercalated nanoplastic is replaced by nanopolyethylene, as follows: A composite photovoltaic cable bridge, comprising the following components, calculated by weight: 70 parts of epoxy resin, 20 parts of carbon fiber, 4 parts of modified yttrium oxide hollow microspheres, 3 parts of nanopolyethylene, 2 parts of plasticizer, 0.3 parts of defoamer, 0.4 parts of antioxidant and 1.5 parts of flame retardant. Nanopolyethylene was purchased from Hubei Xinyuhong Biomedical Technology Co., Ltd., with a CAS number of 9002-88-4.

[0070] Comparative Example 4: The difference between this comparative example and Example 1 is that the intercalated nanoplastic is deleted, specifically as follows: A composite photovoltaic cable bridge, comprising the following components, calculated by weight: 70 parts of epoxy resin, 20 parts of carbon fiber, 4 parts of modified yttrium oxide hollow microspheres, 2 parts of plasticizer, 0.3 parts of defoaming agent, 0.4 parts of antioxidant and 1.5 parts of flame retardant

[0071] Comparative Example 5: The difference between this comparative example and Example 1 is that the modified yttrium oxide hollow microspheres and intercalated nanoplastics are deleted, specifically as follows: A composite photovoltaic cable bridge, comprising the following components, calculated by weight: 70 parts of epoxy resin, 20 parts of carbon fiber, 2 parts of plasticizer, 0.3 parts of defoaming agent, 0.4 parts of antioxidant and 1.5 parts of flame retardant

[0072] Test example: The test items and basis are as follows.

[0073] 1. Dielectric constant-GB / T 5597-1999.

[0074] 2. Compressive strength-GB / T 50081-2019.

[0075] 3. Tensile strength-GB / T1040-1992.

[0076] 4. Flame retardant grade-ASTM635-2003.

[0077] 5. Impact strength-GB / T 1843-2008.

[0078] The test results are shown in Table 1.

[0079] Table 1. Test data of the experimental example

[0080]

[0081] Result analysis: Analyze examples 1-4 and combine the data in Table 1 and Figure 1-3 It can be seen that the composite photovoltaic cable bridge prepared by the present invention has excellent mechanical properties (compressive strength, tensile strength, impact strength), insulation (dielectric constant) and flame retardant properties.

[0082] Analyze Example 1 and Comparative Examples 1-5 and combine the data in Table 1 and Figure 1-4 It can be seen that the addition of modified yttrium oxide nano-microspheres can significantly improve the insulation (dielectric constant), compressive strength and tensile strength of the composite photovoltaic cable bridge. After epoxy resin and modified yttrium oxide hollow microspheres are mixed, the modified yttrium oxide hollow microspheres are combined with epoxy resin, and the multilayer structure formed by the modified yttrium oxide hollow microspheres in the epoxy resin matrix significantly prolongs the permeation path of water molecules and increases the difficulty of water molecules to penetrate, thereby improving the barrier performance of the composite photovoltaic cable bridge, reducing the water absorption rate of the composite photovoltaic cable bridge, and improving its stability in a humid environment, that is, the electrical insulation and compressive strength of the composite photovoltaic cable bridge remain stable. When the crack encounters the modified yttrium oxide hollow microspheres, the direction of the crack will be deflected, extending the crack path, increasing the ability of the composite photovoltaic cable bridge to resist fracture, that is, improving the tensile strength of the composite photovoltaic cable bridge; the modified yttrium oxide hollow microspheres improve the overall tensile strength of the composite photovoltaic cable bridge by strengthening the internal connection of the epoxy resin matrix, making it more difficult to be pulled apart.

[0083] Analyze Example 1 and Comparative Examples 1-5 and combine the data in Table 1 and Figure 4 It can be seen that the addition of modified yttrium oxide hollow microspheres and intercalated nanoplastics improves the flame retardancy of composite photovoltaic cable trays. Modified yttrium oxide hollow microspheres provide physical insulation, epoxy resin forms a chemical carbon layer, and intercalated nanoplastics enhance the barrier properties of the carbon layer. Epoxy resin, modified yttrium oxide hollow microspheres and intercalated nanoplastics complement each other in structure and work synergistically to build a powerful flame retardant system and improve the flame retardant grade of composite photovoltaic cable trays.

[0084] Analyze Example 1 and Comparative Examples 1-5 and combine the data in Table 1 and Figure 1-4 It can be seen that when the modified yttrium oxide hollow microspheres are used alone, the toughness (impact strength) of the composite photovoltaic cable bridge is reduced. This is because the modified yttrium oxide hollow microspheres are prone to rupture when subjected to external forces, thereby reducing the toughness (impact strength) of the composite photovoltaic cable bridge. When epoxy resin, modified yttrium oxide hollow microspheres and intercalated nanoplastics are present at the same time, they can synergistically improve the toughness (impact strength) of the composite photovoltaic cable bridge. The epoxy resin, modified yttrium oxide hollow microspheres and intercalated nanoplastics reinforce the carbon layer to improve the toughness (impact strength) of the composite photovoltaic cable bridge. The nanoplastic layer can provide additional robustness, and when these plastic layers exist in the form of intercalation, they can more effectively disperse stress, thereby improving the toughness of the material.

[0085] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0086] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A composite photovoltaic cable bridge, characterized in that: The invention comprises the following components, calculated by weight: 70 parts of epoxy resin, 20 parts of carbon fiber, 3-5 parts of modified yttrium oxide hollow microspheres, 2-4 parts of intercalated nano plastics, 1-3 parts of plasticizer, 0.2-0.4 parts of defoamer, 0.3-0.5 parts of antioxidant and 1-2 parts of flame retardant.

2. The composite photovoltaic cable tray according to claim 1, characterized in that: The preparation method of the modified yttrium oxide hollow microspheres is as follows: A1. Add 9.8 g of formaldehyde solution and 200 mL of water into a flask, stir magnetically, heat in a water bath to 80°C, add 2.5 g of melamine into the flask, wait for complete dissolution, add formic acid to adjust the pH value of the system in the flask to 6; keep stirring for 1 min, continue stirring for 15 min, wash several times with water and ethanol by centrifugation, and dry at 60°C to obtain melamine-formaldehyde template microspheres; A2, add 0.8mmol of yttrium nitrate hexahydrate into a small beaker containing 30mL of deionized water, stir magnetically to dissolve the yttrium nitrate hexahydrate; then add 3g of urea into the small beaker, and after a clear solution is formed, add 0.2g of the melamine-formaldehyde template microspheres obtained in A1, ultrasonically treat for 25min, transfer to a flask, heat to 85°C in a water bath, stir to react for 2.8h, wash several times with water and ethanol by centrifugation, dry at 60°C, and calcine to obtain a white powder; A3. The white powder obtained in A2 was placed in 0.1 mol / L hydrochloric acid, kept at 43°C for 25 min, washed with deionized water for several times, and dried at 60°C to obtain modified yttrium oxide hollow microspheres.

3. The composite photovoltaic cable tray according to claim 2, characterized in that: In A1, the speed of magnetic stirring is 62-75 r / min; in A2, the speed of magnetic stirring is 45-55 r / min, the calcination heating rate is 2°C / min, the calcination temperature is 800°C, and the calcination time is 2h.

4. The composite photovoltaic cable tray according to claim 1, characterized in that: The preparation method of the intercalated nano plastic is as follows: B1. Add 30 g of sodium montmorillonite into a 1000 mL flask filled with 600 mL of distilled water, heat to 80°C, add 10 g of 1831 intercalation agent, react at constant temperature for 2 h, wash with distilled water until neutral, filter, dry at 80°C, and crush to obtain powder d; B2. Under nitrogen protection, 100 mL of heptane was added to the flask, stirred at 70 r / min, 20 g of d powder was added, and then 30 mL of a heptane solution containing 0.5 g of 2,6-diacetylpyridine-bis-2,4,6-trimethylanilino ferric chloride catalyst was added dropwise, and the reaction was continued for 6 h to obtain a slurry; B3. After emptying the 2L polymerization reactor with nitrogen, add 0.5L hexane, and under stirring at 300r / min, add the slurry obtained in B2 and 0.6g of co-catalyst AlEt3 under the flow of hexane, and add a total of 1L of hexane; close the vent valve, pass ethylene gas at a predetermined polymerization temperature, maintain the polymerization pressure at 1.0MPa, and the polymerization time is 2h. Open the vent valve, cool, discharge, filter, wash with 95% ethanol, and vacuum dry at 60°C to obtain intercalated nanoplastics.

5. The composite photovoltaic cable tray according to claim 1, characterized in that: Said plasticizer comprises stearate plasticizer or phthalate plasticizer.

6. The composite photovoltaic cable bridge according to claim 1, characterized in that: The antioxidant includes a phenolic antioxidant or an amine antioxidant.

7. The composite photovoltaic cable tray according to claim 1, characterized in that: The defoaming agent is polydimethylsiloxane.

8. The composite photovoltaic cable bridge according to claim 1, characterized in that: The flame retardant is a mixture of hexabromocyclododecane, aluminum oxide and ammonium polyphosphate in a mass ratio of 1:1:

2.

9. A method for preparing a composite photovoltaic cable tray according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Evenly mix 70 parts of epoxy resin, 20 parts of carbon fiber, 3-5 parts of modified yttrium oxide hollow microspheres, 2-4 parts of intercalated nanoplastics, 1-3 parts of plasticizer, 0.2-0.4 parts of defoamer, 0.3-0.5 parts of antioxidant, and 1-2 parts of flame retardant, and mix at a mixing temperature of 160-171° C. to obtain a blend; S2, conveying the blend of step S1 to a twin-screw extruder, and granulating at a working temperature of 160-180° C. to obtain a composite material; S3, sending the composite material obtained in step S2 into an injection molding machine, melting it at 170-180° C., injecting it into a mold, and cooling it to obtain a composite material photovoltaic cable bridge.

10. An application of the composite photovoltaic cable bridge according to any one of claims 1 to 8, characterized in that: The composite material photovoltaic cable bridge is used as a supporting structure for photovoltaic cables.